Força e equilíbrio musculares, qualidade de vida e índices plasmáticos de interleucina-6 em idosas da comunidade com osteoartrite de joelho - Mary Luci Avelar di Sabatino Santos (2007)
Osteoarthritis (OA) is a common disease in the elderly population worldwide. It mostly affects the knee and predominates among women. It is the most frequent cause of disability among the elderly and is more prevalent among this population. Affected individuals experience a health condition that dynamically interacts with their activities and participation in personal and environmental aspects. Variability of individual conditions associates the characteristics of each person to aspects of bodily structures and functions. Both the beginning and the progression of the disease are multi-factorial, varying with age, hormone levels, genetic factors, biomechanical alterations and joint inflammation processes. Studies have demonstrated that the production of inflammatory mediators (cytokines) increases when joints are exposed to greater shear forces and overload, resulting in greater joint wear, as in OA. The severity of joint cartilage degeneration has been associated to the elevation of cytokines, including IL-6, which is considered a predictor of sarcopenia, changes in functional capacity and fragility. Obesity is considered an aggravating factor of OA and has considerable impact on radiographic alterations and sarcopenia. Thus, the aim of the present study was to investigate and correlate IL-6 plasma levels in elderly individuals with knee osteoarthritis to muscle force, muscle balance and functionality. A cross-sectional study was carried out on 80 elderly individuals (71.2±5.3 years) from the community with knee OA. Peak torque/mass was measured to establish muscle strength. The agonist/antagonist ratio at speeds of 60°/s and 180°/s was determined on a Biodex isokinetic dynamometer in order to establish muscle balance. Functionality was assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC); x-rays were classified using the Kellgren-Lawrence criteria; BMI (Kg/m2) and IL-6 plasma levels were determined using the ELISA method (Quantikine HS, R&D Systems, Minneapolis, USA). Spearmans coefficient and Mann-Whitney associations were used for the correlations, with the significance level set at p<0.05. There was an inverse correlation between peak torque/mass of knee flexors and extensors at 60º/s and 180°/s, in the hamstring/quadriceps (H/Q) ratio and in BMI with all WOMAC domains. The strongest correlations occurred between the extensor muscles of the knee at 60º/s (r=-0.478; p=0.000) and BMI (r=0.348; p=0.002) with the self-reported function domain. IL-6 levels were significantly correlated with body weight (r=0.250; p=0.025); with the BMI (r=0.215; p=0.056); with peak torque/mass in flexion to the right at 180º/s, (r=-0.232; p=0.03); with the is (H/Q) ratio to the right at 180º/s (r=0.254; p=0.023); and with average peak H/Q torque (r=-0.266; p=0.018). Radiographic OA severity wasnt correlation with the WOMAC or IL6 levels. It was concluded that reduced muscle strength and H/Q balance, obesity and high IL6 levels were associated to reduced functionality in the sample studied.